STRATEGIES FOR WRITING SCIENTIFIC ARTICLES FOR PUBLICATION IN SINTA-ACCREDITED JOURNALS: A LITERATURE REVIEW - Natis Sutisna; B. Herawan Hayadi; Miftahul Ilmi; Siti Mahfudoh; Akhmad Jonny Irawan; Rukiyah Rukiyah (Yayasan Education and Social Center, 2026)
The publication of scientific articles in Science and Technology Index (SINTA)-accredited journals is an important indicator in measuring the academic productivity of lecturers, students, and researchers in Indonesia. Although the number of accredited journals continues to increase, the acceptance rate of articles still faces various challenges, including low manuscript quality, lack of research novelty, methodological weaknesses, and inconsistencies between the articles' focus and scope and the intended journal. This study aims to analyze and synthesize various strategies for writing scientific articles that increase the likelihood of publication in SINTA-accredited journals. The study used the Systematic Literature Review (SLR) method, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were obtained from scientific articles published in the 2021–2025 period through the Google Scholar, Garuda, DOAJ, Crossref, and ResearchGate databases. Articles that met the inclusion criteria were analyzed using content analysis and thematic analysis techniques. The study results indicate that the success of scientific article publication is influenced by several key factors, namely the ability to identify research gaps and research novelty, the preparation of informative titles and abstracts, the development of an introduction based on the research problem, the use of a strong and transparent methodology, the preparation of critical results and discussions, and the use of up-to-date and relevant references. Furthermore, the ethical use of technologies such as Mendeley, Zotero, Publish or Perish, VOSviewer, Grammarly, and generative artificial intelligence has been proven to improve the quality and efficiency of the scientific article writing process. This study concludes that successful publication in SINTA-accredited journals requires a combination of research quality, the authors' academic competence, the use of supporting technology, and an understanding of the editorial and peer-review processes. The findings of this study are expected to serve as guidelines for lecturers, students, and researchers to improve the quality of scientific articles and enhance opportunities for publication in reputable national journals.